The influence of Ceo and board members’ religious affiliation on auditor choice - Rahayu Abdul Rahman,; Lilis Maryasih,; Rita Meutia,; Nor Balkish Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper investigates how the religious affiliation of a firm’s top leaders, CEO, and board members determines auditor choice selection. In particular, this study aims to study the impact of Muslim CEOs and Muslim boards of directors on auditor choice decisions of listed firms in Malaysia. A firm-year observations from 2017 to 2019 are 1,892 listed firms on Malaysian Stock Exchange were employed to scrutinise the impact of religion on the choice of appointing an auditor. Two proxies of religious affiliation which are Muslim CEO and Muslim board members were examined to represent the impact of religion. A logistic regression model results show a significant and favourable association between selecting high-quality audit firms, the percentage of Muslim directors on the board, the Muslim CEO, and religious affiliation proxies. According to the findings, Malaysian listed companies with Muslim CEOs and a sizable percentage of Muslims on their boards are likelier to use Big 4 audit firms to signify high-quality audits. As this study is one of the first empirical studies to explore the role of Muslim CEOs and Muslim board members in Malaysian firms' auditor selection, the findings are helpful to investors, policymakers, and regulators as it offers an understanding of the roles of the religious affiliation of the firm’s top leaders in promoting demand for high audit quality.